Improving the land development system for housing in Hyderabad Pakistan, with particular reference to the HDA Joint Venture Projects - Hussain, Shahid; Archer, Ray W.; Amin, A.T.M. Nurul; Yap, Kioe Sheng; Foo Tuan Seik; The Canadian International Development Agency {CIDA} (Bangkok : Asian Institute of Technology, 1992)
In order to avoid the lengthy and expensive procedure of compulsory land acquisition for its land subdivision projects the Hyderabad Development Authority {HDA) designed the joint venture Scheme (JVS), for cooperative projects with private landowners. But inspite of its apparent superiority in compari son with other methods of land development only three JVS projects have been carried out since 1987, and private landown ers and developers are not showing interest in participating in new projects. This study outlines, reviews and assesses the JVS technique and project experience in order to identify and assess its strengths and weaknesses, and then recommends on improvement measures to make it acceptable for wider use . The three projects carried out met with success and demon strated the feasibility of JVS in the Hyderabad context. The landowners obtained the best possible return through these projects within a reasonable period of time, compared to their own private land subdivision projects. In the case of the HDA's costs and benefits from the projects, its money cost was nil and it acquired land for public facilities at no cost to the government. The plot purchaser's· interest was protected with respect to their investment' compared with their bad expe rience with many private land development projects. Most of the goals of the JVS technique have been satisfactorily met . The study revealed that the use and acceptability of JVS in Hyderabad was badly affected by the prevailing rules and prac tices of HDA, by the inefficient finance system for land development, and by other institutional constraints. It was also hindered by bureaucratic inertia, the civic strife preva lent during 1989-91 in the city, and the landowners inertia to sell their land. The study recommends a number of easy-to-implement measures to improve the JVS technique covering improvement in cost recovery performance; appropriate planning and layout stand ards; more effective targetting of plot marketing, ; efficient coordination of the different participants in the projects; increased landowner's role; and HDA level project approval. The study recommends some more difficult-to-implement proposals requiring policy changes, such as introduction of JVS legisla tion; amendment of the Sindh Disposal of Plot Ordinance; bank ing reforms and tax relief measures. These measures will increase the effectiveness of JVS thereby making it more ac- ceptable and effective for wider use to improve land develop ment for housing in Hyderabad.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science
Thesis (M. Sc.) - Asian Institute of Technology
Keywords: Real estate development -- Pakistan -- Hyderabad